2009
DOI: 10.1185/03007990903094106
|View full text |Cite|
|
Sign up to set email alerts
|

Are intranasal corticosteroids all equally consistent in managing ocular symptoms of seasonal allergic rhinitis?

Abstract: While additional prospective head-to-head clinical trials comparing the efficacy of INS in treating ocular symptoms of AR are needed to fully elucidate the benefits of one INS compared with another, data available to date suggest that not all INS are equally consistent in managing ocular symptoms of SAR. Fluticasone furoate is currently the most consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 50 publications
1
47
0
1
Order By: Relevance
“…This is consistent with the study by Keith et al who reviewed and compared various studies analyzing the efficacy of intra nasal corticosteroids in relieving the ocular symptoms of allergic rhinitis in which he concluded that various intra nasal steroids differed in their efficacy in controlling the ocular symptoms of allergic rhinitis and concluded that fluticasone furoate seemed to be the most effective in this regard. 13 There was a statistically significant reduction in the TNSS by 2 weeks in both the groups, which was maintained till the 3 rd month (p=0.000 in group A and p=0.000 in group B). There was no difference in the score between both the groups till 3 rd month (p=0.431), proving that both the drugs are equally efficacious in reducing the nasal symptoms of allergic rhinitis.…”
mentioning
confidence: 87%
“…This is consistent with the study by Keith et al who reviewed and compared various studies analyzing the efficacy of intra nasal corticosteroids in relieving the ocular symptoms of allergic rhinitis in which he concluded that various intra nasal steroids differed in their efficacy in controlling the ocular symptoms of allergic rhinitis and concluded that fluticasone furoate seemed to be the most effective in this regard. 13 There was a statistically significant reduction in the TNSS by 2 weeks in both the groups, which was maintained till the 3 rd month (p=0.000 in group A and p=0.000 in group B). There was no difference in the score between both the groups till 3 rd month (p=0.431), proving that both the drugs are equally efficacious in reducing the nasal symptoms of allergic rhinitis.…”
mentioning
confidence: 87%
“…The efficacy of FF administered for 4 weeks versus placebo has also been assessed in adolescents and adults with perennial allergic rhinitis, with significant improvement in nasal symptoms and extraocular manifestations (such as pharyngeal or palatal itching) and in the RQLQ scores Keith & Scadding, 2010).…”
Section: Fluticasone Furoatementioning
confidence: 99%
“…But unlike other intranasal corticosteroids, which show contradictory effects on ocular symptoms, FF is the only intranasal corticosteroid that demonstrates a consistent positive effect on ocular symptoms in seasonal allergic rhinitis in a large number of patients from different studies, across different pollen seasons and geographical locations Keith & Scadding, 2010).…”
Section: Fluticasone Furoatementioning
confidence: 99%
“…A comprehensive assessment of all available data in the public domain (including government- and regulatory institution-registered trials) was performed to determine the consistency of INSs in treating the ocular symptoms of AR [45]. This review examined 35 randomized, double-blind, placebo-controlled clinical trials that investigated the effects of BDP, budesonide, ciclesonide, flunisolide, FF nasal spray (FFNS), FP, MF or TA in patients with SAR [45].…”
Section: Introductionmentioning
confidence: 99%
“…This review examined 35 randomized, double-blind, placebo-controlled clinical trials that investigated the effects of BDP, budesonide, ciclesonide, flunisolide, FF nasal spray (FFNS), FP, MF or TA in patients with SAR [45]. Studies had a ≥2-week duration; patients were ≥6 years of age (the majority were ≥12 years of age).…”
Section: Introductionmentioning
confidence: 99%